2021
DOI: 10.1038/s41392-021-00603-6
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of meplazumab in healthy volunteers and COVID-19 patients: a randomized phase 1 and an exploratory phase 2 trial

Abstract: AbstractsRecent evidence suggests that CD147 serves as a novel receptor for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Blocking CD147 via anti-CD147 antibody could suppress the in vitro SARS-CoV-2 replication. Meplazumab is a humanized anti-CD147 IgG2 monoclonal antibody, which may effectively prevent SARS-CoV-2 infection in coronavirus disease 2019 (COVID-19) patients. Here, we conducted a randomized, double-blinded, placebo-controlled phase 1 trial to evaluate the safety, tolerab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 24 publications
0
55
0
3
Order By: Relevance
“…In many clinical trials, the duration of viral shedding has been used as a primary outcome to evaluate the antiviral effect of treatments with lopinavir and ritonavir ( 11 ), hydroxychloroquine ( 38 , 39 ), and meplazumab ( 40 ). Because the viral load of SARS-CoV-2 peaks on or before symptom onset in many patients ( 18 ), and the mean interval between symptom onset and hospitalization is estimated to be 4.64 d ( 41 ), it is expected that antiviral treatments initiated after symptom onset will not shorten the duration of viral shedding.…”
Section: Discussionmentioning
confidence: 99%
“…In many clinical trials, the duration of viral shedding has been used as a primary outcome to evaluate the antiviral effect of treatments with lopinavir and ritonavir ( 11 ), hydroxychloroquine ( 38 , 39 ), and meplazumab ( 40 ). Because the viral load of SARS-CoV-2 peaks on or before symptom onset in many patients ( 18 ), and the mean interval between symptom onset and hospitalization is estimated to be 4.64 d ( 41 ), it is expected that antiviral treatments initiated after symptom onset will not shorten the duration of viral shedding.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to a previous report which identified basigin as a coreceptor for SARS-CoV-2, showed binding of RBD to spike via SPR assays and ELISA, and showed that meplazumab, an anti-basigin MAb, could neutralize SARS-CoV-2 ( 10 ). The use of an anti-basigin MAb in clinical trials has begun on the basis of the original observation that basigin may be required for host cell entry ( 30 ). We believe that it is necessary to proceed with caution when interpreting the trial data, as further investigation is warranted to determine what role, if any, basigin has in the SARS-CoV-2 invasion process.…”
Section: Discussionmentioning
confidence: 99%
“…Initial evaluation of meplazumab, an anti-basigin antibody, for treatment of SARS-CoV-2 pneumonia suggested that there could be a benefit ( 30 ). These results are based on small groups ( n = 17 in the treatment group) ( 30 ); as such, it will be necessary to conduct larger clinical studies to confirm this finding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations